2023
DOI: 10.1002/brb3.3062
|View full text |Cite
|
Sign up to set email alerts
|

rTMS treatment for abrogating intracerebral hemorrhage‐induced brain parenchymal metabolite clearance dysfunction in male mice by regulating intracranial lymphatic drainage

Abstract: Background The discovery of the glymphatic system and meningeal lymphatic vessels challenged the traditional view regarding the lack of a lymphatic system in the central nervous system. It is now known that the intracranial lymphatic system plays an important role in fluid transport, macromolecule uptake, and immune cell trafficking. Studies have also shown that the function of the intracranial lymphatic system is significantly associated with neurological diseases; for example, an impaired intracranial lympha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Ischemic and hemorrhagic strokes have also been investigated in terms of their effect on the glymphatic system [25,[34][35][36][37][38][39][40][41][42][43][44][45][46]. See Supplemental Table 2 for an overview of the 14 included articles spanning 10 animal and 4 human studies.…”
Section: Strokementioning
confidence: 99%
“…Ischemic and hemorrhagic strokes have also been investigated in terms of their effect on the glymphatic system [25,[34][35][36][37][38][39][40][41][42][43][44][45][46]. See Supplemental Table 2 for an overview of the 14 included articles spanning 10 animal and 4 human studies.…”
Section: Strokementioning
confidence: 99%
“…In addition to using drugs or biologics, clearing obstructed glymphatic channels has also been achieved in animal models using mechanical methods such as focused ultrasound treatment in combination with microbubbles (FUS-MB) ( 122 ), and non-invasive neuronal stimulation techniques, such as transcranial magnetic stimulation (TMS) or multisensory stimulation ( 228 , 229 ). A recent study using the 5xFAD AD mouse model showed that treatment with FUS-MB led to enhanced solute Aβ clearance from the brain, first into the CSF space and then into the deep cervical lymph nodes, which correlated with improved memory functions ( 122 ).…”
Section: Considerations In the Study And Clinical Use Of Brain-border...mentioning
confidence: 99%